Hot Water Extraction Improves the Characteristics of Willow and Sugar Maple Biomass With Different Amount of Bark - Therasme, Obste; Volk, Timothy A.; Cabrera, Antonio M.; Eisenbies, Mark H.; Amidon, Thomas E. (Frontiers in Energy Research, 2018)
Shrub willows are being developed as a short rotation woody crop (SRWC) that can grow on marginal agricultural land. Willow has a high net energy ratio (energy produced/ fossil fuel energy consumed), low greenhouse gas footprint and high carbohydrate production potential. Willow biomass can be combined with forest biomass, but willow often has a higher proportion of bark that creates challenges because it increases the ash content and decreases the melting point. Hot water extraction is a pretreatment that has been shown to improve the quality of chipped material while producing a marketable stream of byproducts. This study evaluated how the amount of bark (0%, 33%, 66% and 100%) on three willow cultivars and sugar maple impact the output of hot water extraction in terms of mass removal and extract composition, as well as its influence on the heating value, ash and elemental content. The hot water extraction process resulted in ash content up to 50% for sugar maple and willow, but there was variation among the willow varieties. The heating value after hot water extraction was about 5% higher because of the removal of mostly hemicelluloses, which have relatively low heating value. HWE led to significant reductions of calcium, potassium, magnesium and sulfur contents. The hot water extraction provides a fermentable sugar stream and other co-products after multiple separation and treatment steps, and improves the characteristics of willow and sugar maple biomass for combined heat and power. This paper demonstrates how biomass with higher bark content can generate a useable sugar stream while improving the quality of the biomass for combined heat and power by managing its ash content while simultaneously producing other valuable products.